THE EFFECT OF EARNINGS, BOOK VALUE, R&D EXPENDITURE, AND CASH FLOW INFORMATION ON STOCK PRICES - Kinanti Ananda; Rini Indriani (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the effect of earnings per share (EPS), book value per share (BVPS), research and development expenditure per share (R&DPS), and operating cash flow per share (OCFPS) on stock prices of healthcare, consumer, and basic materials companies listed on the Indonesia Stock Exchange during the period 2015–2024. The research method employed is a quantitative approach using panel data regression analysis with a Random Effects Model (REM) estimated through Generalized Least Squares (GLS). The sample consists of 13 firms selected through purposive sampling, resulting in 124 firm-year observations after the removal of outliers. The results indicate that EPS has a positive and significant effect on stock prices at the 5% significance level, while BVPS has a positive and significant effect at the 10% significance level. In contrast, OCFPS and R&DPS do not have a significant effect on stock prices, and firm size as a control variable is also found to be insignificant. In conclusion, earnings remain the most value-relevant accounting information in explaining stock prices in the Indonesian capital market, whereas book value exhibits weaker explanatory power and both operating cash flow and R&D expenditure are not fully reflected in market valuation. Keywords: Earnings per Share (EPS), Book Value per Share (BVPS), Research and Development Expenditure, Operating Cash Flow per Share (OCFPS), Stock Prices